Cooperative Anti-Invasive Effect of Cdc42/Rac1 Activation and ROCK Inhibition in SW620 Colorectal Cancer Cells with Elevated Blebbing Activity - de Toledo, Marion; Anguille, Christelle; Roger, Laureline; Roux, Pierre; Gadea, Gilles (PLOS ONE, 2012)
Rho GTPases are key regulators of tumour cell invasion and therefore constitute attractive targets for the design of anticancer agents. Several strategies have been developed to modulate their increased activities during cancer progression. Interestingly, none of these approaches took into account the existence of the well-known antagonistic relationship between RhoA and Rac1. In this study, we first compared the invasiveness of a collection of colorectal cancer cell lines with their RhoA, Rac1 and Cdc42 activities. A marked decrease of active Cdc42 and Rac1 correlated with the high invasive potential of the cell lines established from metastatic sites of colorectal adenocarcinoma (LoVo, SKCo1, SW620 and CoLo205). Conversely, no correlation between RhoA activity and invasiveness was detected, whereas the activity of its kinase effector ROCK was higher in cancer cell lines with a more invasive phenotype. In addition, invasiveness in these colon cancer cell lines was correlated with a typical round and blebbing morphology. We then tested whether treatment with PDGF to restore Cdc42 and Rac1 activities and/or with Y27632, a chemical inhibitor of ROCK, could decrease the invasiveness of SW620 cells. The association of both treatments substantially decreased the invasive potential of SW620 cells and this effect was accompanied by loss of membrane blebbing, restoration of a more elongated cell morphology and re-establishment of E-cadherin-dependent adherens junctions. This study paves the road to the development of therapeutic strategies in which different Rho GTPase modulators are combined to modulate the cross-talk between Rho GTPases and their specific input in metastatic progression.